( u n ) : ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ u 0 = − 1 u 1 = 3 , ∀ n ≥ 1 u n − 5 u n − 1 + 6 u n − 2 = 2 n 2 + 2 n + 1
Consider the recurrence relation above.
If u n can be expressed as u n = a b n + c d n + e n k + f n l + g , type your answer as a + b + c + d + e + f + g + k + l
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Linear Recurrence Relations - Problem Solving
u n = n ( n + 8 ) − 3 5 . 2 n + 5 . 3 n + 1 + 1 9
To see how to solve a recurrence relation, see this .For the solution itself, it is just the same as this but see the 1st link or else the second will overwhelm you
Problem Loading...
Note Loading...
Set Loading...
m a x i m u m p o w e r o f n i s 2 i n u n − 5 u n − 1 + u n − 2 ⇒ { k , l } = { 2 , 1 } u n − 5 u n − 1 + u n − 2 = 2 n 2 + 2 n + 1 = a b n − 2 ( b 2 − 5 b + 6 ) + c d n − 2 ( d 2 − 5 d + 6 ) + e [ n 2 − 5 ( n − 1 ) 2 + 6 ( n − 2 ) 2 ] + f [ n − 5 ( n − 1 ) + 6 ( n − 2 ) ] + ( g − 5 g + 6 g ) = a b n − 2 ( b 2 − 5 b + 6 ) + c d n − 2 ( d 2 − 5 d + 6 ) + e ( 2 n 2 − 1 4 n + 1 9 ) + f ( 2 n − 7 ) + 2 g c o m p a r e c o e f f i c i e n t s o f n , ( b 2 − 5 b + 6 ) = ( d 2 − 5 d + 6 ) = 0 ; ⇒ { b , d } = { 3 , 2 } 2 e = 2 , − 1 4 e + 2 f = 2 , 1 9 e − 7 f + 2 g = 1 ⇒ e = 1 , f = 8 , g = 1 9 p u t t h e s e v a l u e s i n g i v e n e q u a t i o n s , u 0 = a + c + 1 9 = − 1 ; u 1 = 3 a + 2 c + 2 8 = 3 ⇒ a = 1 5 , c = − 3 5 ⇒ A n s = a + b + c + d + e + f + g + k + l = 1 5 + 3 − 3 5 + 2 + 1 + 8 + 1 9 + 2 + 1 = 1 6